Parenting stress among parents of children with autism spectrum disorder: the need of stress management guidelines and policy - Noor Aishah Rosli,; Zarinah Mohd Kasirun,; Mohd Hairul Nizam Md Nasir,; Fazidah Othman,; Tengku Sarina Aini Tengku Kasim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This concept paper reviews the issue of parenting stress in mothers and fathers of children with Autism Spectrum Disorder (ASD), and highlights the need for stress management guideline and policy for these parents in Malaysia. Many studies have shown that parents of children with ASD are experiencing a high level of stress. Despite this issue, there has not been any local measures to improve the well-being of the parents. In Malaysia, there is no policy or standard guideline for parents of children with ASD, hence maintaining the risk of mental health cases among them. In order to overcome this issue, this paper reviewed the Lazarus and Folkman’s (1984) problem-focused strategies used by parents of children with ASD from previous studies. The strategies mentioned in this paper had been empirically proven as reducing the parents’ stress level. This paper also recommends the strategies to be included in a local policy to help the parents manage their stress.